Assessing Educational Tourism’s Capacity to Support Sustainable Principles via the ELT Framework: A Systematic Review - Eldo Delamontano; Cipta Endyana; Yunus Winoto; Evi Novianti (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This Systematic Literature Review (SLR) analyzes research trends in Educational Tourism (2019–2024) by applying Kolb’s Experiential Learning Theory (ELT) framework. The study specifically investigates how the Educational Tourism approach supports the principles of Sustainable Tourism and its positioning in addressing the complex issue of Climate Change. Methodology: The research employed an SLR supported by bibliometric analysis and thematic synthesis of 447 Scopus-indexed articles. The ELT framework (comprising Concrete Experience, Reflective Observation, Abstract Conceptualization, and Active Experimentation) was used as a conceptual lens to test the balance of thematic focus across the literature. Main Findings: The analysis revealed a systemic imbalance within the literature. While the Abstract Conceptualization and Concrete Experience stages show strong documentation, the Reflective Observation is the most minimally discussed theme (65.55%). This gap indicates that current research tends to bypass the critical evaluation process, thus failing to methodologically validate the internal mechanism required to link direct experience to lasting sustainable behavior. This methodological weakness hinders the sector's ability to effectively tackle complex, large-scale issues like Climate Change and Environmental Protection. Novelty/Originality of this study: This study contributes by being the first to systematically apply the ELT framework to diagnose the thematic maturity of Educational Tourism, explicitly identifying Reflective Observation as the most critical theoretical and methodological gap.